Alendronate Improves Bone Mineral Density in Children and Adolescents Perinatally Infected With Human Immunodeficiency Virus With Low Bone Mineral Density for Age. (1st October 2019) - Jacobson, Denise L; Lindsey, Jane C; Gordon, Catherine; Hazra, Rohan; Spiegel, Hans; Ferreira, Flavia; Amaral, Fabiana R; Pagano-Therrien, Jesica; Gaur, Aditya; George, Kathy; Benson, Jane; Siberry, George K
Abstract: Background: Children and adolescents with perinatal human immunodeficiency virus (HIV) infection and with low bone mineral density (BMD) may be at higher risk of osteoporosis and fractures in later life than their uninfected peers. Bisphosphonate therapy has been shown to reduce fractures in adults with osteoporosis, but has not been formally studied in youths living with HIV. Methods: Fifty-two children and adolescents (aged 11–24 years) perinatally infected with HIV with low lumbar spine (LS) BMD ( Z score < −1.5) were randomized to receive once-weekly alendronate or placebo in a double-blind cross-over study designed to assess the safety and efficacy of 48 and 96 weeks of alendronate in the United States and Brazil. All participants received daily calcium carbonate and vitamin D supplementation and were asked to engage in regular weight-bearing exercise. Safety and efficacy are summarized for the initial 48 weeks of the trial. Results: Grade 3 or higher abnormal laboratory values, signs, or symptoms developed in 5 of 32 (16%) participants on alendronate and 2 of 18 (11%) on placebo ( P > .99). No cases of jaw osteonecrosis, atrial fibrillation, or nonhealing fractures were reported. Mean increases (95% confidence interval) in LS BMD over 48 weeks were significantly larger on alendronate (20% [14%–25%]) than placebo (7% [5%–9%]) ( P < .001). Similar improvements were seen for whole body BMD. Conclusions: In this small study in children and adolescents perinatally infected with HIV with low LS BMD, 48 weeks of alendronate was well-tolerated, showed no safety concerns, and significantly improved LS and whole body BMD compared to participants on vitamin D/calcium supplementation and exercise alone. Clinical Trials Registration: NCT00921557. Abstract : Forty-eight weeks of alendronate with calcium/vitamin D supplementation and exercise in children/adolescents with perinatal HIV infection with low lumbar spine (LS) bone mineral density (BMD) significantly increased LS and whole body BMD compared to supplementation and exercise alone; no safety concerns were identified.